Survey-based insights from choice-based conjoint analyses on customer preferences for company characteristics of life insurers - Moritz Hanika; Nadine Gatzert (Risk Management and Insurance Review, 2024)
Abstract The aim of this paper is to investigate customer preferences for certain company characteristics when purchasing life insurance products. We focus on ratings provided by aggregators, namely financial strength, sustainability, service quality, and type of customer touchpoint (online vs. in person), while also studying potential product-specific differences between annuities and term life policies. Toward this end, we conduct two choice-based conjoint analyses with 529 and 543 German respondents to estimate individual preference structures. Consistent with economic expectations, we observe statistically significant higher preferences for better ratings of the life insurer, which also materialize in the respondents' marginal willingness to pay. One main finding is that customer preferences in our sample are asymmetric, with a strong focus on avoiding below-average ratings. Furthermore, for both annuities and term life insurances, the relatively most important life insurer attribute for customers is financial strength, followed by service quality, sustainability, and type of customer touchpoint.
Keywords: 330